Abdominal aortic aneurysm–the forgotten diagnosis?. Issue 652 (February 1980) - Contini, S.; McMaster, P.
Abstract : A review of all cases of abdominal aortic aneurysm presenting to Addenbrooke's Hospital, Cambridge, in a 4-year period revealed that there were 118 such patients and confirmed the relatively low operative mortality for elective aneurysmal surgery (6.6%) compared with the high mortality (66.6%) for ruptured or leaking abdominal aneurysm. In only 50% of the cases was the correct diagnosis made during the lifetime of the patient; nor was the correct diagnosis always made after admission to hospital. The need for an early and accurate diagnosis of abdominal aneurysms is stressed and an increased awareness of this condition, based on well established clinical features, would undoubtedly reduce the overall mortality.